Analisis Kinerja Keuangan Pemerintah Daerah Sebelum dan Sesudah Otonomi Daerah terhadap Pertumbuhan Ekonomi (Studi di Barlingmascakeb) - Yulian, Tri Nurindahyanti (JURNAL EKONOMI, 2014)
The implementation of regional autonomy in all regencies in Indonesia was marked by the enactment of the Act (the Act) relating to regional autonomy: Law No. 22 of 1999 on Regional Government. With the implementation of regional autonomy, there are two aspects of financial performance required to be better than before the era of regional autonomy. The first aspect is that the area is given the authority to take care of local financing with core strengths in the ability of revenue (fiscal decentralization). The second aspect is the management of regional spending, the financial management area should be more accountable and transparent local demand must be more efficient and effective in the management area.Policy of fiscal decentralization is believed to bring positive influence on economic growth prompting many countries to implement it. Since the regional autonomy and fiscal decentralization in Indonesia enacted, commitment to the implementation of transparency and public accountability began voiced. Public accountability of local government is the provision of information and the disclosure of the activities and financial performance of local governments to the parties concerned. Regional autonomy and fiscal decentralization expects local governments have greater independence in the financial area. Therefore the role of PAD is critical to the region's financial performance.The results of this study concluded that there are differences in financial performance in local government in the form of fiscal decentralization Barlingmascakeb on before and after the era of regional autonomy, it is seen from the results of the Paired T-Test Sig. 0.001 <0.05. The difference in the performance of this leads to a worse direction, it can be seen from the ratio of fiscal decentralization down from 0.16284 to 0.11820 after the pre-autonomy autonomy while financial performance in the form of financial independence there is no difference. This is evident from the results of the Paired T-Test Sig. 0.094> 0.05. Assay results obtained OLS regressions with t count the number of Fiscal Decentralization (DF) (-2.485) <- t table (-2.001) and the Sig. DF 0.006 <0.05 we can conclude that fiscal decentralization has a negative effect on economic growth.Key Words: Autonomy, Financial Performance of local government, Fiscal Decentralization, Financial Independence, Economic Growth